3. PEMERINTAHAN SBY DAN PENANGANAN KORUPSI - Astuti, Puji (Faculty of Social and Political Sciences Diponegoro University, 2007)
Corruption was being the most popular issue in Indonesia, because corruption was broken not only law order, but even social value. Corruption in Indonesia have been recognized as the main source of poverty. For this reason, Susilo Bambang Yudhoyono should proved his political agreement to wipe out of corruption. The winning SBY on Pemilu 2004 also because of his political agreementÂ for cleaning corruption as extra ordinary crime. As we realized that corruption in Indonesia have known as a systematic crime, so for handling corruption also need systematic efforts, not only law enforcement and bureaucracy reform, but the most important was how to create culture against corruption.